2021
DOI: 10.3390/molecules26216506
|View full text |Cite
|
Sign up to set email alerts
|

Co-Precipitated Ni-Mg-Al Hydrotalcite-Derived Catalyst Promoted with Vanadium for CO2 Methanation

Abstract: Co-precipitated Ni-Mg-Al hydrotalcite-derived catalyst promoted with vanadium were synthesized with different V loadings (0–4 wt%) and studied in CO2 methanation. The promotion with V significantly changes textural properties (specific surface area and mesoporosity) and improves the dispersion of nickel. Moreover, the vanadium promotion strongly influences the surface basicity by increasing the total number of basic sites. An optimal loading of 2 wt% leads to the highest activity in CO2 methanation, which is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In addition to the metallic nanoparticle-supported oxides, nickel-based double-layered hydroxides (LDHs) have shown excellent catalytic performances towards DRM reaction [27][28][29][30]. Modification of double-layered hydroxides with Y, Zr, and Ce as dopants or promotors significantly improves CH 4 and CO 2 conversions, lowers carbon deposition, and limits side reactions [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the metallic nanoparticle-supported oxides, nickel-based double-layered hydroxides (LDHs) have shown excellent catalytic performances towards DRM reaction [27][28][29][30]. Modification of double-layered hydroxides with Y, Zr, and Ce as dopants or promotors significantly improves CH 4 and CO 2 conversions, lowers carbon deposition, and limits side reactions [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…According to relevant researches, promoters can modify the coordination sphere of the active metal or influence the reaction path to improve catalytic performance. Some promoters such as Ce, [17,18] Zr, [19,20] V, [21,22] Mn, [5,23] and Ti [24,25] have been widely used for adding Ni-based catalysts for CO 2 methanation. In particular, it was revealed that Ti could significantly facilitate the active metal dispersion and inhibit sintering of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is kinetically hindered due to the intrinsic feature of an eight-electron reduction process. , As a result, the reaction is usually carried out at high temperatures (>300 °C), which is thus accompanied by the endothermic RWGSR as a side reaction . Many kinds of catalysts have been developed based on Co, , Ni, Ru, , Rh, , and Pd. , Mechanistic studies indicate that there are two pathways for the methanation of CO 2 , including (a) the conversion of CO 2 to CO by the RWGSR process, followed by hydrogenative methanation of CO and (b) the cascade hydrogenation of CO 2 with the formation of formate as the intermediate . The development of catalysts for the methanation of CO 2 at low temperatures, with both high efficiency and selectivity, is still the focus of this field.…”
Section: Introductionmentioning
confidence: 99%